2021
DOI: 10.1111/jcpt.13387
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of fidaxomicin versus oral vancomycin in the treatment of recurrent clostridioides difficile

Abstract: What is Known and Objective The 2017 IDSA/SHEA Clinical Practice Guidelines for Clostridioides difficile infection (CDI) recommend treating recurrent episodes with fidaxomicin or oral vancomycin, but there is little evidence to support one strategy over another, particularly beyond the first recurrence. The aim of this study was to compare clinical outcomes in patients with recurrent CDI treated with vancomycin vs. fidaxomicin. Methods This retrospective study evaluated inpatients with recurrent CDI treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…For the sensitivity analysis for 28 to 59-day follow-up, the removal of the Rinaldi study evaluating rCDI and mrCDI patients decreased heterogeneity from 58% to 34% without changing the overall RR; the removal of the Guery study decreased heterogeneity from 58% to 45% and yielded a non-significant RR. 9,28 The removal of both the Rinaldi and Guery study decreased heterogeneity to 0%, with a similar RR and tighter CI relative to the original analysis (see Figure A4). For the sensitivity analysis for 60 to 90 day follow-up, heterogeneity decreased to 0% with the exclusion of the Polivkova study resulting in a similar RR (see Figure A5).…”
Section: Includedmentioning
confidence: 84%
See 2 more Smart Citations
“…For the sensitivity analysis for 28 to 59-day follow-up, the removal of the Rinaldi study evaluating rCDI and mrCDI patients decreased heterogeneity from 58% to 34% without changing the overall RR; the removal of the Guery study decreased heterogeneity from 58% to 45% and yielded a non-significant RR. 9,28 The removal of both the Rinaldi and Guery study decreased heterogeneity to 0%, with a similar RR and tighter CI relative to the original analysis (see Figure A4). For the sensitivity analysis for 60 to 90 day follow-up, heterogeneity decreased to 0% with the exclusion of the Polivkova study resulting in a similar RR (see Figure A5).…”
Section: Includedmentioning
confidence: 84%
“…Of the remaining 22 full-text articles reviewed, 14 studies (six RCTs and eight observational trials) met eligibility criteria for the final meta-analysis (Figure 1). [9][10][11][12][20][21][22][23][24][25][26][27][28][29][30] Reasons for excluding full-text articles included an unspecified follow-up period for recurrence, missing data, population overlap, and concomitant use of fecal microbiota transplantation. [31][32][33][34][35][36][37] For included RCTs, three studies were assessed to have a low risk of bias and three with some concerns, primarily due to problems related to the unblinding of standard-of-care treatments (Figure 2A).…”
Section: Re Sultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the absolute reduction in CDI recurrence was similar to the randomized trials. While it should be noted that some observational studies conducted in certain high-risk groups [ 18 , 19 ] have not found a meaningful difference in outcomes between fidaxomicin and vancomycin, several other observational studies conducted by Goldenberg et al [ 20 ], Gallagher et al [ 21 ], and Polivkova et al [ 22 ] have demonstrated fidaxomicin’s superiority over vancomycin in treating CDI. The evidence on the superiority of fidaxomicin over vancomycin has also been acknowledged in the latest update to IDSA guidelines for CDI treatment published in 2021 [ 11 ], which now recommends fidaxomicin as first-line treatment for both initial and recurrent CDI episodes, with vancomycin an acceptable alternative.…”
Section: Discussionmentioning
confidence: 99%
“…From observational studies, both FDX and BZL show lower efficacy from the first and, definitely, the second recurrence [10][11][12]; hence, probably positioning these drugs in the second recurrence and thereafter, provides a sign of their lower efficiency. In the event of a second recurrence and particularly in the subsequent ones, the most effective treatment today is FMT.…”
Section: Recommended Treatmentsmentioning
confidence: 99%